1988
DOI: 10.1530/acta.0.1190139
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hyperthyroidism with a small single daily dose of methimazole

Abstract: A prospective randomized trial with the conventional divided doses (10 mg 3 times daily, N = 29) and a small single daily dose (15 mg once daily, N = 25) of methimazole for the treatment of Graves' hyperthyroidism was performed. Within 8 weeks, almost 80% of the patients in both groups became euthyroid. The mean time required to achieve the euthyroid state was 6.0 \m=+-\2.8 and 6.0 \m=+-\3.8 weeks, respectively. TSH binding inhibitor immunoglobulin was found in about 90% of the patients in both groups before m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 18 publications
1
7
0
2
Order By: Relevance
“…The time interval needed to achieve euthyroidism is defined as the time required for the serum free T4 level to become normal in accordance with our previous report [11]. MMI therapy was stopped in six patients before they reached a euthyroid condition due to adverse reactions (4 in group C, 2 in group S).…”
Section: Treatment With Different MMI Dosage Regimensmentioning
confidence: 71%
See 2 more Smart Citations
“…The time interval needed to achieve euthyroidism is defined as the time required for the serum free T4 level to become normal in accordance with our previous report [11]. MMI therapy was stopped in six patients before they reached a euthyroid condition due to adverse reactions (4 in group C, 2 in group S).…”
Section: Treatment With Different MMI Dosage Regimensmentioning
confidence: 71%
“…Moreover, our previous report [11] was the first to demonstrate that there was no difference between the changes in TBII levels during one year of treatment with conventional doses (10 mg 3 times daily) and a small single daily dose (15 mg once daily) of MMI. Reinwein et al [12] reported that TBII levels decreased to similar levels in patients treated with 10 mg or with 40 mg of MMI during one year of treatment.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A number of studies have consistently shown that treatment of hyperthyroidism with single daily dose of 15–60 mg of MMI is effective in the induction of euthyroidism in 80%−100% of the patients in one to seven months (Greer et al ., 1977; Macfarlane et al ., 1983; Morgan et al ., 1984; Shiroozu et al ., 1986; Arntzenius et al ., 1988; Mashio et al ., 1988; Gupta et al ., 1992; Nicholas et al ., 1995; Page et al ., 1996; Mashio et al ., 1997; Wise et al ., 1973). In addition, the once‐daily dose regimen of 15–30 mg of MMI is not only as effective as the multiple daily dose regimen of either MMI or PTU (Shiroozu et al ., 1986; Mashio et al ., 1988; Nicholas et al ., 1995) but also yields better patients' compliance (Nicholas et al ., 1995). Therefore, single daily dosage of 15–30 mg of MMI is also accepted as an alternative regimen to the divided dose regimen for the treatment of hyperthyroidism (Utiger, 1995; Cooper, 2000).…”
mentioning
confidence: 99%
“…Laboratory tests for thyroid function were assayed as described in a previous report (8). Serum T3, T4, free T3, free T4 and TSHconcentrations were measured by radioimmunoassay or immunoradiometric assay using a commercially available kit.…”
Section: Methodsmentioning
confidence: 99%